Post‐embryonic development of the Early Ordovician (ca. 480 Ma) trilobite Apatokephalus latilimbatus Peng, 1990 and the evolution of metamorphosis. Issue 5 (15th September 2015) - Park, Tae‐Yoon S.; Kihm, Ji‐Hoon
SUMMARY: In many marine invertebrates metamorphosis entails a shift from a free‐swimming larva to a benthic juvenile or adult. However, how the metamorphosis‐entailing "indirect development" in arthropods arose from direct‐developing ancestor is poorly understood. Trilobites left a rich fossil record, and some trilobite lineages had a metamorphosis‐undergoing early developmental stage, termed the "asaphoid protaspis"‐stage, providing a good opportunity to elucidate the rise of indirect development. Among others, the Ordovician representatives of Remopleuridioidea are known to possess a highly bulbous "asaphoid protaspis, " while the Furongian (Late Cambrian) remopleuridioidean genus Haniwa did not possess it. Here we show the post‐embryonic development of the remopleuridioidean trilobite, Apatokephalus latilimbatus, from the Tremadocian (485.4 Ma–477.7 Ma) Dongjeom Formation, Korea. The post‐embryonic development of A. latilimbatus contains a free‐swimming "commutavi protaspis" (a term replacing "asaphoid protaspis"). Interestingly, the earlier protaspid stage shows more similar morphology and size to the meraspis than the commutavi protaspid stage does. This indicates that the commutavi protaspid stage was intercalated into the ancestral direct development as a specialized stage for a better dispersal, and thus the "commutavi protaspis" of A. latilimbatus represents the initial phase of the evolution of indirect development. The duration of the free‐swimming phase became longer in more derived remoplueridioidean trilobites, implying that the intercalated free‐swimming strategy became emphasized during subsequent evolution. The morphological gap between the commutavi protaspis and the subsequent earliest meraspis provides a convincing case for the "selective independence" of developmental stages, explaining the various morphologies of commutavi protaspides in many trilobite lineages.